(untitled) - Eliopoulos, Charlotte (London, 1999)
Manual of gerontologic nursing addresses the challenges and concerns facing nurses in the ever growing field of elder care. Beginning with an overview of the foundation of gerontologic nursing, the book discusses health challenges facing older adults and special issues such as drug therapy, legal risks, and ethical issues. Assessment considerations, care goals, and nursing interventions are provided. Practical information for the care giver is conveniently highlighted in tables and boxes to facilitate learning. This book is an excellent resource for any nurse or student working with the elderly.
Keywords: Geriatric nursing,Điều dưỡng lão khoa